La Foule. Réflexions autour d’une abstraction - Vincent Rubio (Conserveries Mémorielles)
When tracing back to Ancient Greece the history of the intellectual treatment of the crowd in the Western world, one realizes that the ‘crowd itself’ has always been envisaged as an abstraction. All the specific disciplines who took interest the crowd (Philosophy, Literature, Psychology, Sociology, etc.) have systematically pictured the crowd as a sui generis being, a being-in-itself. This assertion is not as banal as it may appear. Gustave Le Bon’s Psychology of Crowds appears as a typical ‘miniature’ not only of crowd psychology as well as a whole body of works which foreran the emergence of that particular discipline in the last decade of the 19th Century, but also ultimately of whatever could be qualified as ‘crowd theory.’ Nonetheless, an analysis of Le Bon’s arguments reveals a tautological reasoning in which ‘the crowd makes the crowd’. Of course, this article does not hold the contention that the crowd has no empirical existence. However, the theoretical problems of the notion invite a reconsideration of its status and its nature as a social fact.